Kontribusi Kesadaran Spiritual dengan Kebahagian Tenaga Kependidikan di Lembaga Pendidikan - Yuzarion Yuzarion; Ahmad Fajar Prasetya; Mujidin Mujidin; Rici Kardo; Mori Dianto (Kuras Institute, 2022)
The purpose of this study was to determine the contribution of spiritual awareness to happiness. This study uses an exploratory method with a quantitative approach. A total of 196 subjects participating in this study were obtained using simple random sampling technique. The data collection uses a spiritual awareness scale and a happiness scale. Hypothesis testing using statistical analysis method of correlation. The results of this study concluded that there is a positive and significant contribution of spiritual awareness to employee happiness. The spiritual awareness that is built strongly in employees will be a driving factor in creating true happiness.